Deteksi Plat Nomor Menggunakan Connected Components dan Pra-Pengolahan untuk Mempercepat Proses Deteksi - Anggraeni, Arlia; Widyassari, Adhika Pramita (Universitas Nusantara PGRI Kediri, 2022)
As the number of vehicles in Indonesia increases, the number of crimes that occur also increases, resulting in an increase in the problem of traffic violations and an increase in the number of vehicle parking activities. Seeing the importance of number plate detection to overcome this, a system that is able to detect number plates quickly and accurately is needed. The segmentation process using Connected Components has better performance when compared to Diff and Fast-RNN methods. Pre-processing is an important step before carrying out a number plate detection. begins by changing the image size using the resizing function and by converting the RGB image into a grayscale image which aims to reduce the image size, thereby speeding up the next process. Then the segmentation process uses the connected components method. The test results on 10 test images produce an accuracy of 80%. In terms of detection time, it shows a decrease. The number plate detection process without using pre-processing takes an average of 3.721519 seconds, whereas when using pre-processing only 1.45731 seconds. It can be concluded that the addition of pre-processing is able to speed up the detection process